Sustainable Use of Extractive Wastes in Continuous Surface Coal Mines: The case of Anyntaion Mine, Greece - Sokratidou, Ariadni; Paraskevis, Nikolaos; Servou, Aikaterini; Pavloudakis, Francis; Roumpos, Christos (Technical Annals, 2024)
Continuous surface coal mines are related to large amounts of extracted overburden or interburden waste material. One of the main objectives of the strategic mine planning of such mines is to optimize the coal production, considering the waste-to-ore ratio in combination with the optimal allocation of the waste material to the outside and inside dumping areas. Further to other uses of waste material, the suitable sustainable reclamation of mining land is directly associated with the sustainable use of waste dumping sites for post-mining activities. This study investigates the main issues related to extractive waste management in continuous surface coal mining projects, focusing on a long-term strategic mining planning and scheduling model and the post-mining utilization of waste dumping areas. As a case study, the basic geospatial parameters of the waste dumping areas of the Amyntaion lignite mine in North Greece are examined based on the results of a long-term experimental design of water and soil sampling and monitoring program. The applied methods include a model for validating lignite production and waste extraction and dumping scheduling, as well as the geotechnical, hydrogeological, and geochemical spatial analysis of the waste material, considering post-mining land uses and circular economy principles. The findings indicate the geotechnical and geochemical stability of the examined areas and the suitability of mining land to transition to post-mining activities, mainly related to renewable energy systems.